2019
DOI: 10.1002/ijc.32051
|View full text |Cite
|
Sign up to set email alerts
|

Independent and joint associations of blood lipids and lipoproteins with lung cancer risk in Chinese males: A prospective cohort study

Abstract: To investigate the independent and joint associations of blood lipids and lipoproteins with lung cancer risk in Chinese males, a prospective cohort study was conducted. A total of 109,798 males with baseline information on total cholesterol (TC), triglycerides (TG), low‐density lipoprotein cholesterol (LDL‐C), high‐density lipoprotein cholesterol (HDL‐C) and non‐HDL were prospectively observed from 2006 to 2015 for cancer incidence. Cox proportional hazards models and restricted cubic spline (RCS) analysis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 42 publications
1
58
0
1
Order By: Relevance
“…Moreover, as for the lipids profiles, recent evidence indicated that higher high-density lipoprotein cholesterol level is protective against the lung cancer, whereas higher triglyceride is associated with higher lung cancer incidence [ 36 ], and these findings are confirmed by a subsequent case–control study in Chinese patients with and without non-small cell lung cancer [ 37 ]. However, a recent prospective cohort study showed that the association between triglyceride and lung cancer risk may be more complicated than expected and presented as a U-shaped association [ 38 ]. In addition, results regarding the association between hypertension and lung cancer risk are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as for the lipids profiles, recent evidence indicated that higher high-density lipoprotein cholesterol level is protective against the lung cancer, whereas higher triglyceride is associated with higher lung cancer incidence [ 36 ], and these findings are confirmed by a subsequent case–control study in Chinese patients with and without non-small cell lung cancer [ 37 ]. However, a recent prospective cohort study showed that the association between triglyceride and lung cancer risk may be more complicated than expected and presented as a U-shaped association [ 38 ]. In addition, results regarding the association between hypertension and lung cancer risk are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…The Hexokinase method was used for the measurement of fasting blood glucose (FBG). The details of the measurement of blood lipids, including total cholesterol (TC), triglycerides (TG), low‐density lipoprotein cholesterol (LDL‐C), and high‐density lipoprotein cholesterol (HDL‐C) have been introduced in previously published studies 42 …”
Section: Methodsmentioning
confidence: 99%
“…We followed participants beginning at the baseline examination and ending at the occurrence of cancer, death, or 31 December 2015, whichever event came first. The details of cohort follow‐up and cancer assessment have been published previously 42. In brief, people with cancer were identified through biennial health examinations and annual searches of the Tangshan medical insurance system and the Kailuan social security system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data were obtained from the Kailuan Cohort Study of China, which is a health examination of employees of the Kailuan Company in Tangshan City in Hebei Province, about 90 miles southeast of Beijing. In the past few decades, Kailuan Group has developed a comprehensive company that manages coal production, machine manufacturing, transportation, chemical production, education, and healthcare, etc The methodology for the Kailuan study have been described previously . In short, since May 2006, more than 13 000 people over the age of 18 have participated in biennial questionnaire interviews and clinical examinations at 11 hospitals affiliated with Kailuan Company.…”
Section: Methodsmentioning
confidence: 99%